Social partners’ involvement in pension reform in the EU - Duchemin, Claire; Weber, Tina (Dublin, 2013)
"The reform of pension systems is arguably one of the key challenges for social policy in Europe in the context of demographic change. In recent years, the issue has been very high on the policy agenda across all EU Member States and in Norway. While several countries have introduced pension reforms over a decade ago, the economic crisis and the ensuing debt crisis have prompted a further wave of reform. These have largely concentrated on the sustainability of public pensions and on increasing the effective retirement age, with some changes proving very controversial. This report provides an overview of the involvement of social partners in pension reforms adopted since 2008 across the EU27, as well as in Norway. It focuses particularly on the influences of the social partners on the outcomes of reform processes. This report distinguishes between reforms of statutory ‘pay-as-you go’ pensions and other funded schemes (such as statutory funded schemes, occupational pensions and other private schemes)."